An ex ante evaluation of targeted fertilizer recommendations for Ethiopian cereal producers - Oyinbo, Oyakhilomen; Chamberlin, Jordan (EiA, 2024)
Agricultural extension systems in settings with variable landscape positions, such as foot slopes, midslopes and hill slopes often provide fertilizer use recommendations that do not take into account variability in landscape positions. While the limited consideration of landscape positions in agricultural extension programming may partly explain the low and variable agronomic and economic returns to fertilizer use, empirical evidence under farmer conditions is thin. In this report, we document preliminary findings from an ex ante evaluation of landscape-targeted fertilizer recommendations for sorghum, teff and wheat production in Ethiopia. We use data from a farm-household survey and on farm validation trials complemented with geospatial soil, rainfall, crop and fertilizer price data from secondary sources. Results show that yield response to and profitability of fertilizer is, on average, low and varies across landscape positions. In addition, fertilizer application appears marginally more profitable on foot slopes and mid-slopes compared with hill slopes, irrespective of the cereal type. Furthermore, fertilizer application under landscape-based fertilizer recommendations seems marginally more profitable compared with fertilizer application under farmer current fertilizer application and current extension fertilizer recommendations, indicating that landscape-targeted fertilizer advisories may contribute to improving returns to fertilizer. Overall, we note that substantially improving fertilizer use efficiency and investment returns would likely require a holistic approach, involving soil health and agronomic management, market and institutional considerations, beyond landscape-targeted fertilizer advisories